2015
DOI: 10.1007/s13277-015-3540-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LDHA suppresses tumor progression in prostate cancer

Abstract: A key hallmark of cancer cells is their altered metabolism, known as Warburg effect. Lactate dehydrogenase A (LDHA) executes the final step of aerobic glycolysis and has been reported to be involved in the tumor progression. However, the function of LDHA in prostate cancer has not been studied. In current study, we observed overexpression of LDHA in the clinical prostate cancer samples compared with benign prostate hyperplasia tissues as demonstrated by immunohistochemistry and real-time qPCR. Attenuated expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 18 publications
3
72
1
Order By: Relevance
“…LDHA catalyzes the conversion of pyruvate to lactate and is considered to be a key checkpoint of anaerobic glycolysis (9). Increased levels of LDHA have been reported in several types of tumors (11,(13)(14)(15), and its expression levels have been correlated with clinical stages in breast cancer, renal cell carcinoma and prostate cancer; these reports further support that therapies targeting LDHA may provide useful strategies for controlling cancer progression. Moreover, previous reports using data from the Oncomine database showed that the mRNA levels of LDHA were up-regulated in GBM compared to those in matched normal tissues; these results prompted us to determine the correlation between LDHA expression levels and glioma malignancy (16).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…LDHA catalyzes the conversion of pyruvate to lactate and is considered to be a key checkpoint of anaerobic glycolysis (9). Increased levels of LDHA have been reported in several types of tumors (11,(13)(14)(15), and its expression levels have been correlated with clinical stages in breast cancer, renal cell carcinoma and prostate cancer; these reports further support that therapies targeting LDHA may provide useful strategies for controlling cancer progression. Moreover, previous reports using data from the Oncomine database showed that the mRNA levels of LDHA were up-regulated in GBM compared to those in matched normal tissues; these results prompted us to determine the correlation between LDHA expression levels and glioma malignancy (16).…”
Section: Discussionmentioning
confidence: 84%
“…In renal cell carcinoma, knocking down LDHA resulted in potential anticancer effects (14). Although the abnormal expression of LDHA has been reported in several cancers (10)(11)(12)(13)(14)(15), little is known about the expression pattern of LDHA and its underlying roles in GBM. Previous reports using data from the Oncomine database showed that the mRNA levels of LDHA were up-regulated in GBM compared to matched tissues (16); these finding prompted us to examine the underlying role of LDHA in glioma malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Alpha-enolase (ENO1) promotes cell glycolysis, growth, migration, and invasion in non-small cell lung cancer through FAK-mediated PI3K/AKT pathway [15], and ENO1 is confirmed as a novel substrate of FBXW7 in colorectal cancer [16]. Lactate dehydrogenase A (LDHA) acts as oncogenic role in prostate cancer [17]. Aldolase A (ALDOA) may provide good survival prediction for stage I-IV colorectal cancer patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Lactate dehydrogenase A (LDHA) catalyzes the final step of glycolysis in which pyruvate is directly converted to lactate, indicating the critical role for maintaining glycolysis in tumorigenesis [14] . It has been reported that the expression of LDHA is abnormal in many human cancers, such as prostate cancer [15] , ovarian cancer [16] , pancreatic cancer [17,18] and breast cancer [19] . Meanwhile, inhibition of LDHA reduced several tumor progression [14][15][16][17] , indicating the underlying role of LDHA as a promising target for cancer therapy.…”
mentioning
confidence: 99%
“…It has been reported that the expression of LDHA is abnormal in many human cancers, such as prostate cancer [15] , ovarian cancer [16] , pancreatic cancer [17,18] and breast cancer [19] . Meanwhile, inhibition of LDHA reduced several tumor progression [14][15][16][17] , indicating the underlying role of LDHA as a promising target for cancer therapy. In breast cancer, silence of LDHA suppresses tumorigenicity through induction of oxidative stress-mediated mitochondrial pathway apoptosis [19] .…”
mentioning
confidence: 99%